MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN DAN HASIL BELAJAR SISWA MUATAN BAHASA INDONESIA MENGGUNAKAN MODEL AGUNA PADA SISWA KELAS IV SDN BENUA ANYAR 3 BANJARMASIN - Giswari, Fitriani; Sari, Dessy Dwitalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to address the low levels of student activity, reading comprehension skills, and learning outcomes in Indonesian language subjects among fourth-grade students at SDN Benua Anyar 3. The problems were attributed to non-student-centered teaching, a lack of reading activities, and a limited variety of learning models that support text comprehension. To overcome these issues, the AGUNA learning model was implemented. The research employed a qualitative Classroom Action Research (CAR) approach, conducted over four sessions during the second semester of the 2024/2025 academic year with 11 students as subjects. Data was collected through observations of teacher and student activities, as well as written tests to measure reading comprehension skills and learning outcomes. The results showed significant improvements. Teacher activity improved to